Modification of lipase by polyethylene glycol - Basri, M.; Salleh, A.B.; Ampon, K.; Yunus, W.M.Z.; Razak, C.N.A. (Informa Healthcare, 1991)
Lipase was modified using polyethylene glycol activated by p-nitrochloroformate. The hydrolytic activity of the polyethylene glycol-derivatised lipase (PEG-lipase) was relatively low compared with that of the unmodified enzyme in aqueous system. The esterification activity, however, was enhanced following the modification. The rate of esterification of butyric acid was higher than that of oleic acid. Benzene was the best solvent for the esterification reaction. © 1991 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.